2016
DOI: 10.1208/s12248-016-9999-6
|View full text |Cite|
|
Sign up to set email alerts
|

Intra-articular Injection of Urinary Bladder Matrix Reduces Osteoarthritis Development

Abstract: Micronized porcine urinary bladder matrix (UBM) is an extracellular matrix biomaterial that has immunomodulatory and pro-regenerative properties. The objective of this study was to assess the ability of UBM to alter disease progression in a mouse model of post-traumatic osteoarthritis (OA). Ten-week-old wild-type C57BL/6 male mice underwent anterior cruciate ligament transection (ACLT) to induce OA. Two weeks after ACLT, UBM (50 mg/mL) or saline was injected into the mouse joint. At 4 and 8 weeks post-ACLT, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…muscle repair, IL-4 production by Th2 cells was required for the myeloid cell transition to a proregenerative phenotype, needed for efficient muscle repair (102). In the joint, IL-4 production correlated with tissue repair after ACLT, suggesting that similar mechanisms of type 2 immune responses impact OA (103). Without treatment, OA signatures reflect a profibrotic and proinflammatory immune response that is potentially mediated by SnCs, which may only recruit and modulate the phenotypes of immune cells.…”
Section: R E V I E W S E R I E S : C E L L U L a R S E N E S C E N C mentioning
confidence: 99%
“…muscle repair, IL-4 production by Th2 cells was required for the myeloid cell transition to a proregenerative phenotype, needed for efficient muscle repair (102). In the joint, IL-4 production correlated with tissue repair after ACLT, suggesting that similar mechanisms of type 2 immune responses impact OA (103). Without treatment, OA signatures reflect a profibrotic and proinflammatory immune response that is potentially mediated by SnCs, which may only recruit and modulate the phenotypes of immune cells.…”
Section: R E V I E W S E R I E S : C E L L U L a R S E N E S C E N C mentioning
confidence: 99%
“…Besides joint damage, MIA injection induces mechanical sensitivity of the ipsilateral hind paw and weight bearing deficit. Histological observation and pain-related behavior in rat models together resemble human degenerative OA (Jacobs et al 2017).…”
Section: Introductionmentioning
confidence: 87%
“…Osteoarthritis (OA) is the most noticeable form of the synovial joint disease, characterized by joint degeneration and pain. In addition to structural defects, there is increasing evidence that approximately 30% of OA patients have neuropathic pain (Teeple et al 2013;Wang and Regatte 2015;Rey-Rico et al 2016;Jacobs et al 2017;Jin et al 2017;Philpott et al 2017). The mechanisms of persistent pain development are not yet clear, but most of modern OA treatment strategies are based on pain management (Ma et al 2009;Van Velden et al 2015;Philpott et al 2017;Zhang et al 2017;Kalamegam et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the presence and integrity of basement membrane complex in UBM promotes inductive tissue remodeling (Brown and Badylak, 2014 ), but little is known about the supporting activity of UBM toward chondrocyte function. UBM was recently used for articular cartilage regeneration in canine and murine models demonstrating its efficacy in treating dogs or mice with chronic osteoarthritis of the hip or knee joint, respectively (Rose et al, 2009 ; Tottey et al, 2011 ; Jacobs et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%